Pengaruh Penambahan Vitamin C pada Suplementasi Besi Folat dalam Meningkatkan Kadar Hemoglobin pada Pasien Pasca Seksio Sesarea di RSU PKU Muhammadiyah Klaten - Angganis, Yunisa Dwi (Jurnal Kedokteran Indonesia, 2009)
Background: Sectio-caesarian (SC) proportion was high at Indonesian hospitals such as RS CiptoMangun Kusumo Jakarta (35.7%) and RSU PKU Muhammadiyah Klaten (33.8%). Massive blood loss dueto SC may cause women at risk for iron-deficiency anemia after birth delivery. This study aimed todetermine if adding vitamin C to Fe folate supplementation further increase hemoglobin level.Methods: A double-blinded randomized controlled trial was conducted at PKU Muhammadiyah Klaten,Central Java. A sample of 32 anemic women after SC birth delivery were alllocated to either experimentalgroup or control group. All study subjects were given capsules containing 200mg ferrous sulphate and0.25mg folic acid. In addition, the experimental subjects received 100mg vitamin C. These capsuleswere taken once daily for 60 days. Hemoglobin level was measured by Cyanmethemoglobin. Foodintake during experiment was recorded by 24 hour food recall. To control for confounding variablesafter randomization, the incremental effect of adding vitamin C to Fe Folate on hemoglobin wasanalyzed by multiple linear regression model on Stata intercooled 7.Results: Adding vitamin C to Fe folate increased hemoglobin level as much as 7.9 g/l higher than Fefolate alone, and it was statistically significant (b = 7.9; p = 0.013; CI95% 1.9 to 14.1), after controlling forage and food intake such as Fe, folic acid, vitamin C, protein, and energy, during experimentation.Conclusion: Adding vitamin C to Fe folate signficantly increases hemoglobin level in anemic womenafter sectio-caesarian birth delivery. Hospitals are recommended to provide Fe Folate + vitamin Csupplementation for anemic women after sectio-caesarian birth delivery to increase hemoglobinlevel.Keywords: anemia, hemoglobin, sectio-caesaria, vitamin C, Fe folate, women giving birth